Benthic and Substrate Category Profile of Coral Reef in Labuan Pandan Waters, East Lombok - Noar Muda Satyawan; Novita Tri Artiningrum (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Coral reefs are unique ecosystems and only occur in the tropics area. One of the coral reef distribution in Indonesia is Lombok Island. The coral reefs in Lombok Island under degradation conditions caused by natural and human activities. The purpose of this study was to provide an overview of the benthic profile and substrate of coral reefs in the Labuhan Pandan waters, Eastern Lombok. Observations were conducted in March 2019 at 5 stations using the Underwater Photo Transect (UPT) method. The results showed that in general benthic coral reefs were dominated by Acropora Branching (35.40%) then followed by Soft Coral (20.89%), DCA (14.08%), Coral Foliose (11.07%), Rubble (7.36%) and Halimeda (2.77%). The highest percentage of Acropora Branching were found at KND_01 station (63.33%) followed by PTG_01 (49.13%), PTG_02 (31.18%), BDR_01 (21.73%), and PTG_03 (11.00%). The highest DCA percentage was found at BDR_01 station (29.27%) while Soft Coral was found dominant at PTG_02 (47.67%). Halimeda was only found in PTG_02 (1.87%) and PTG_03 (12.00%). Differences in the composition of benthic and substrate may be caused by differences in water conditions at each station.